2023
DOI: 10.3390/w16010042
|View full text |Cite
|
Sign up to set email alerts
|

Water and Sediment Chemistry as Drivers of Macroinvertebrates and Fish Assemblages in Littoral Zones of Subtropical Reservoirs

Linton F. Munyai,
Thendo Liphadzi,
Thendo Mutshekwa
et al.

Abstract: Reservoirs are human-made ecosystems with diverse purposes that benefit humans both directly and indirectly. They however cause changes in geomorphological processes such as sediment cycling and influence the composition and structure of aquatic biota. This study aimed to identify water and sediment quality parameters as drivers of macroinvertebrates and fish communities during the cool-dry and hot-wet seasons in the littoral zones of three subtropical reservoirs (Albasini, Thathe and Nandoni). Macroinvertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Macroinvertebrates are an important part of aquatic ecosystems, and community structure characteristics are related to environmental variables (Munyai et al, 2024). As such, we revealed that changes in water chemistry variables were not reflected in the macroinvertebrate communities, whereas sediment chemistry variables were important as a predictor of macroinvertebrates.…”
Section: Discussionmentioning
confidence: 70%
“…Macroinvertebrates are an important part of aquatic ecosystems, and community structure characteristics are related to environmental variables (Munyai et al, 2024). As such, we revealed that changes in water chemistry variables were not reflected in the macroinvertebrate communities, whereas sediment chemistry variables were important as a predictor of macroinvertebrates.…”
Section: Discussionmentioning
confidence: 70%